Simplicity Beneath Complexity: Counting Molecular Electrons Reveals Transients and Kinetics of Photodissociation Reactions. Issue 19 (1st April 2019) - Ruddock, Jennifer M.; Zotev, Nikola; Stankus, Brian; Yong, Haiwang; Bellshaw, Darren; Boutet, Sébastien; Lane, Thomas J.; Liang, Mengning; Carbajo, Sergio; Du, Wenpeng; Kirrander, Adam; Minitti, Michael; et al.
Abstract: Time‐resolved pump–probe gas‐phase X‐ray scattering signals, extrapolated to zero momentum transfer, provide a measure of the number of electrons in a system, an effect that arises from the coherent addition of elastic scattering from the electrons. This allows to identify reactive transients and determine the chemical reaction kinetics without the need for extensive scattering simulations or complicated inversion of scattering data. We examine the photodissociation reaction of trimethylamine and identify two reaction paths upon excitation to the 3p state at 200 nm: a fast dissociation path out of the 3p state to the dimethyl amine radical (16.6±1.2 %) and a slower dissociation via internal conversion to the 3s state (83.4±1.2 %). The time constants for the two reactions are 640±130 fs and 74±6 ps, respectively. Additionally, it is found that the transient dimethyl amine radical has a N−C bond length of 1.45±0.02 Å and a C−N−C bond angle of 118°±4°. Abstract : Excitation leading to separation : The photodissociation of trimethylamine is investigated using time‐resolved pump–probe gas‐phase X‐ray scattering measurements. Two reaction paths that follow excitation to the 3p state are identified: a fast dissociation path to the dimethyl amine radical and a slower dissociation via internal conversion to the 3s state.